Use of Electrospun Phenylalanine/Poly-ε-Caprolactone Chiral Hybrid Scaffolds to Promote Endothelial Remodeling - Sun, Benlin; Hou, Lei; Sun, Binbin; Han, Yu; Zou, Yunqing; Huang, Juexin; Zhang, Yanan; Feng, Chuanliang; Dou, Xiaoqiu; Xu, Feng (Frontiers in Bioengineering and Biotechnology, 2021)
The fabrication of tissue-engineered vascular grafts (TEVGs) to replace damaged vessels is a promising therapy for cardiovascular diseases. Endothelial remodeling in the lumen of TEVGs is critical for successful revascularization. However, the construction of well-functioning TEVGs remains a fundamental challenge. Herein, chiral hybrid scaffolds were prepared by electrospinning using D/L-phenylalanine based gelators (D(L)PHEG) and poly-ε-caprolactone (PCL). The chirality of scaffolds efficiently affected the endothelial remodeling progress of TEVGs. Compared with L/PCL and PCL, D/PCL scaffolds enhanced cell adhesion, proliferation, and upregulated the expression of fibronectin-1 and vinculin. These results suggests that chiral hybrid scaffolds can promote endothelial remodeling of TEVGs by upregulating adhesion-associated protein levels. This study offers an innovative strategy for endothelial remodeling of TEVGs by fabricating chiral hybrid scaffolds, and will provide new insight for the treatment of cardiovascular diseases.